Differences in the demographic characteristics of highly materialistic consumers and those whose clothing consumption practices reflect material simplicity - Erasmus, Alet C. (Aletta Catharina) (University of Pretoria, 2019)
Dissertation (MConsumer Science)--University of Pretoria, 2018.